Factors Influencing PUS Women on the Selection of Long-Term Contraceptive Methods (MKJP) at Puskesmas Lamno, Jaya District, Aceh Jaya Regency - Amalia, Nonny; Theo, Deli; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2024)
Family Planning (KB) policy aims to control population growth by reducing birth rates. However, many women experience difficulty in choosing the appropriate type of contraception. This study aims to analyze the factors that influence women of childbearing age (WUS) in choosing a long-term contraceptive method (MKJP). The design of this research is an analytical survey with a cross-sectional approach. The sample for this research was 95 WUS mothers who were selected by accidental sampling. Data was collected through primary and secondary data and analyzed using the binary logistic regression test. The research results show that knowledge, attitudes, husband's support, and socio-cultural factors have a significant influence on the selection of MKJP. However, the role of health workers does not have a significant influence. This research concludes that knowledge, attitudes, husband's support, and socio-cultural factors influence the selection of MKJP, while the role of health workers has no influence. It is hoped that these results can serve as a guide for family planning service officers to improve WUS knowledge and attitudes and provide comprehensive contraception.